A Note on the Effects of Yoghurt Acid Whey Marination on the Tenderness and Oxidative Stability of Different Meat Types - Panagiotis Simitzis; Fotini Zikou; Dionisis Progoulakis; Georgios Theodorou; Ioannis Politis (Foods, 2021)
The aim of this preliminary study was to examine the effects of yoghurt acid whey (YAW) marination on quality parameters and the oxidative stability of pork, lamb, rabbit and chicken meat. Twenty-four samples per meat type were randomly allocated to one of four groups: CON, without any treatment; YAW1 and YAW2, where samples were marinated for 20 h at 4 °C at a pH of 5 or 4.5, respectively; and YAW3, where samples were treated as in the YAW2 group except hesperidin was also added at the level of 2 g/L. As indicated, meat tenderness was improved as a result of YAW marination, apart from the chicken samples. In general, values of pH, redness and yellowness were decreased after immersion in YAW both in raw and cooked samples. However, lightness was increased in the raw meat samples as a result of YAW marination, though this effect was not observed in the cooked meat samples with the exception of chicken meat. Chroma values were higher in controls compared to YAW-treated groups in raw pork and lamb meat, while no significant differences regarding chroma were found among groups in cooked lamb and rabbit meat. Hue angle values were greater in YAW-treated groups compared to controls in raw samples, whereas no significant differences among groups were indicated in cooked meat. Meat oxidation rates were not affected by treatment with YAW and the hesperidin addition, which improved the oxidative stability of lamb and chicken meat. Thus, YAW marination could be recommended as a novel strategy that improves meat tenderness without negative effects on the other quality characteristics.